Toxoplasma gondii: Comparison of a rhoptry-ELISA with IFAT and MAT for antibody detection in sera of experimentally infected pigs - Garcia, João Luis; Navarro, Italmar Teodorico; Vidotto, Odilon; Gennari, Solange Maria; Machado, Rosângela Zacarias [UNESP]; Pereira, Ademir Benedito da Luz; Sinhorini, Idercio Luiz (Elsevier, 2006)
Indirect ELISA and IFAT have been reported to be more sensitive and specific than agglutination tests. However, MAT is cheaper, easier than the others and does not need special equipment. The purpose of this study was to compare an enzyme linked immunosorbent assay using crude rhoptries of Toxoplasma gondii as coating wells (r-ELISA) with indirect fluorescence antibody test (IFAT) and modified agglutination test (MAT) to detect anti-T. gondii antibodies in sera of experimentally infected pigs. Ten mixed breed pigs between 6.5 and 7.5 weeks old were used. All pigs were negative for the presence of T. gondii antibodies by IFAT (titre < 16), r-ELISA (OD < 0.295) and MAT (titre < 16). Animals received 7 × 107 viable tachyzoites of the RH strain by intramuscular (IM) route at day 0. Serum samples were collected at days -6, 0, 7, 14, 21, 28, 35, 42, 50, and 57. IFAT detected anti-T. gondii antibodies earlier than r-ELISA and MAT. The average of antibody levels was higher at day 35 in IFAT (Log10 = 2.9) and in MAT (Log10 = 3.5), and at day 42 in r-ELISA (OD = 0.797). The antibody levels remained high through the 57th day after inoculation in MAT, and there was a decrease tendency in r-ELISA and IFAT. IFAT was used as gold standard and r-ELISA demonstrated a higher prevalence (73.3%), sensitivity (94.3%), negative predictive value (83.3%), and accuracy (95.6%) than MAT. Kappa agreements among tests were calculated, and the best results were shown by r-ELISA × IFAT (κ = 0.88, p < 0.001). Cross-reaction with Sarcocystis miescheriana was investigated in r-ELISA and OD mean was 0.163 ± 0.035 (n = 65). Additionally, none of the animals inoculated with Sarcocystis reacted positively in r-ELISA. Our results indicate that r-ELISA could be a good method for serological detection of T. gondii infection in pigs. © 2005 Elsevier Inc. All rights reserved.
Keywords: Apicomplexa; ELISA; enzyme linked immunosorbent assay; IFAT; indirect fluorescence antibody test; MAT; modified agglutination test; Pig; Rhoptry antigens; Toxoplasma gondii; Toxoplasmosis; antibody; diagnostic agent; immunoglobulin G; membrane protein; protozoon antibody; ROP 1 protein, Toxoplasma gondii; agglutination test; animal cell; animal experiment; animal tissue; antibody blood level; antibody detection; antibody titer; blood sampling; calculation; controlled study; cross reaction; diagnostic accuracy; diagnostic value; fluorescent antibody technique; inoculation; intermethod comparison; nonhuman; priority journal; Sarcocystis; serodiagnosis; swine; animal; animal parasitosis; biosynthesis; blood; comparative study; female; immunology; isolation and purification; male; methodology; prediction and forecasting; prevalence; randomization; sensitivity and specificity; time; Toxoplasma; Animalia; Sarcocystis miescheriana; Sus scrofa; Agglutination Tests; Animals; Antibodies, Protozoan; Enzyme-Linked Immunosorbent Assay; Female; Fluorescent Antibody Technique, Indirect; Immunoglobulin G; Male; Membrane Proteins; Predictive Value of Tests; Prevalence; Random Allocation; Sensitivity and Specificity; Swine; Time Factors; Toxoplasmosis, Animal